How is peer, self and teacher-assessment perceived and understood by students in an MFL context? - Bull, Joseph (2013)
Teachers spend a huge amount of time assessing students work. In this research project, I investigate student response to teacher feedback, and compare this with two alternatives to teacher-led assessment. These are peer assessment techniques, where the key assessment tasks are completed by fellow students, and self-assessment, where students assess their own work. I conducted a series of interviews with students and teachers to attempt to understand exactly what was communicated by these forms of feedback. The research shows that students have a far less clear understanding of all forms of feedback than is commonly assumed by their teachers, and that significant modifications in practice are necessary if students are to benefit fully from the feedback provided to them. However, the research suggests the possibility that undertaking peer and self-assessment activities may assist students in developing their understanding sufficiently to allow them to benefit from other forms of assessment.